Populações microbianas e antagonismo de actinobactérias sobre rizóbios em solos do semiárido - Lima, José Vinícius Leite (2017)
The structure of the communities living in the soil is driven by various mechanisms and the ecological interactions established between the living organisms. In the same way, the components of the microbiota present harmonic or non-harmonic relationships, for example, between actinobacteria and rhizobia. Interspecific competition among microorganisms occurs when many species require the same resources, and the negative effect on the availability of common resources adversely affects the others. In this context, the objective of this study was to quantify the microbial population in the soil and leaf litter in the vegetation of the caatinga and carrasco in the Brazilian semiarid region (Chapter I) and to characterize and evaluate the antagonistic effect of actinobacteria on rhizobia (Chapter II). The soil samples were collected at the Ecological Station of Aiuaba (Aiuaba, Ceará), characterized by the vegetation of caatinga and carrasco. In chapter I, the population density of the microbial community was evaluated by sampling of soil and litter in the vegetation of caatinga and carrasco at the Aiuaba Ecological Station. The microorganisms were isolated from the soil samples in flasks containing 0.8% saline solution and cultured, after consecutive dilutions, in culturing media specific to cultivable populations of total bacteria, actinobacteria, cellulolytic bacteria, phosphate solubilizing bacteria and fungi. Population estimation was then performed by standard counting on plates and the values were expressed in CFU.g-1. The microbial populations from the soil and leaf litter differed each other quantitatively and in the two vegetations, but in general were greater in the leaf litter. Thus, the knowledge of the population structure of the microbial community can be extended to the semiarid soils. In Chapter II, the strains of actinobacteria isolated in the first study were characterized and tested for “in vitro” inhibitory effect on strains of rhizobia also isolated from semiarid soils. The actinobacteria were purified in their respective culture medium (CDA medium). The strains were characterized for their color and morphology of the colonies, tolerance to pH levels, production of melanin and use of carbon sources. The “in vitro” antagonism of actinobacteria on rhizobia was evaluated in Petri dish containing yeast mannitol agar (YMA) medium by the formation of inhibition zone. The actinobacteria and rhizobia that had greater antagonistic effect or did not presented inhibition zones were molecularly identified. Sixty strains were identified in seven genera of actinobacteria in which had tolerance to variations in pH, low melanin production and generalist use of carbon sources. It was also observed “in vitro” antagonism of actinobacteria species, standing out the genus Streptomyces, on strains of Rhizobium tropici, Bradyrhizobium yuanmingense and two other rhizobia strains not identified. This is the first work that addresses this ecological interaction between microorganisms of the Brazilian semiarid region and reveals the occurrence of new species related to this negative interaction. Thus, the presence of antagonism among these organisms may lead to “in vivo” studies, contributing to future agricultural and/or ecological uses.